Role of Neoadjuvant Chemotherapy in High-Grade Neuroendocrine Carcinoma of the Uterine Cervix - Hyerim Eum; Yoon-Kyung Shin; Ju-Hyun Kim; Yong Man Kim; Jong-Hyeok Kim; Dae-Shik Suh; Dae-Yeon Kim; Jeong-Yeol Park (Clinical and Experimental Obstetrics & Gynecology)
Background: This study aimed to assess the feasibility and efficacy of neoadjuvant chemotherapy (NACT) in treating patients with high-grade neuroendocrine carcinoma of the uterine cervix (HGNEC). Methods: We performed a retrospective case-control study at Asan Medical Center, Seoul, Republic of Korea, from January 1993 to December 2017, involving 60 patients with surgically treated HGNEC. Thirteen patients (21.7%) received NACT before undergoing surgery. Regarding the comparison between the group that underwent NACT and the group that did not, we used a propensity score-matched analysis, matching 22 patients in the primary radical surgery group with 11 patients in the neoadjuvant chemotherapy followed by radical hysterectomy group. Results: In the entire cohort, primary open surgery was more common in the primary surgery group compared to the NACT group (p = 0.004). After propensity score matching (PSM), the median tumor size was 3.5 cm in the primary surgery group and 2.4 cm in the NACT group (p = 0.078). After matching, there was no significant difference in the recurrence rate between the two groups (63.6% in the primary surgery group vs. 63.6% in the neoadjuvant chemotherapy group, p = 0.782). After PSM, the primary surgery group exhibited a lower intraoperative transfusion rate (10%) than the NACT group (45.5%, p = 0.052). Conclusions: While NACT was feasible in patients with HGNEC, it did not significantly improve the survival rate over primary radical surgery.